Child-rearing practices in Barrio Cruz-na-Ligas.[article]. - oming, Maria Fe A.
This study was conducted in Barrio Cruz-na-Ligas, a semi-rural community in Diliman, Quezon City. Nineteen mothers and thirty-eight children took part on this study. It is investigated the socialization of nine behavior patterns: aggression, succorance, obedience, achievement-orientation responsible performance of duty, sociability, nurturance, dominance and self-reliance. For each of these patterns of behavior, two problems were posed; Firstly, how is the behavior socialized by the mothers to their children? Secondly, how is the behavior manifested by the children in their varying day-to-day interactions and how is this related to the mothers rearing practices? The third problem calls for the interrelation of the training for one pattern of behavior with the others. The methods use in this study were the following: participant observation, key informant technique, systematic interview of children, mother interview, and the child verbal Thematic Apperception Test(doll play). It was found that in many instances there is a close relationship between child-rearing practices and the behavior of the children, However, other variables also affect the behavior of the children: among those noted are the child's level of development and the cultural context in which the child lives. In the many, therefore, child-rearing practices, although they may wield some influences on the behavior of the children. are only one of the many factors that affect the resultant personality of the child.